SURVEI DAN PEMETAAN UNSUR HARA N, P, K, DAN pH TANAH PADA LAHAN SAWAH TADAH HUJAN DI DESA DURIAN KECAMATAN PANTAI LABU - Sukma Triharto; Lahuddin Musa; Gantar Sitanggang (Jurnal Agroekoteknologi, 2014)
The objective of this research are to survey and to map the nutrients which is nitrogen (N),phosphate (P), and potassium (K) and the soil pH of rain fed lowland in Desa Durian KecamatanPantai Labu. The soil analysis was conducted in Research and Technology Laboratory inAgricultural Faculty of North Sumatra University on July – November 2013. The researchconducted the survey grid method semi-detailed lavel with 1 sample each 250 meter observationdensity. For the nutrient the researcher used Khejdhal method for soil total nitrogen, Extraction HCl25% for soil Potential phosphate, extraction 1 N NH4OAc pH 7 for soil potassium exchange, forsoil pH the researcher used electrometric method, and the result will be interpreted on nutrientstatus map. The result showed that total nitrogen is classified into two status, low nitrogen (582,048Ha) and medium nitrogen (167,952 Ha). Potential phosphate is classified into very low status (750Ha). And potassium exchange is classified into three status, medium potassium (137,202 Ha), highpotassium (515,303 Ha) and very high potassium (97,495 Ha). Soil pH classified into aciditytendency.Key Words: Soil survey, nutrient status mapping, rain fed lowland.